If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 7 = 15y Reorder the terms: 7 + y = 15y Solving 7 + y = 15y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-15y' to each side of the equation. 7 + y + -15y = 15y + -15y Combine like terms: y + -15y = -14y 7 + -14y = 15y + -15y Combine like terms: 15y + -15y = 0 7 + -14y = 0 Add '-7' to each side of the equation. 7 + -7 + -14y = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -14y = 0 + -7 -14y = 0 + -7 Combine like terms: 0 + -7 = -7 -14y = -7 Divide each side by '-14'. y = 0.5 Simplifying y = 0.5
| 8x^3-36x^2+48x-16=0 | | 5.7x^2-3.2x=2 | | 6x-(3x+7)=17 | | 4+2n=7 | | 2(x-2)-3(2x-5)=3x+7 | | 6x-9-8x=9-x+3 | | 5x-8+3x+4=x+7 | | 3(x-2)=5(x+3) | | 8(3*1.6-5)= | | 8(3a-5)= | | 3x-5=5x+3 | | 3x-5=6x+3 | | (a-11)(a+11)= | | 8(x+8)=64 | | 9x^2+30x+7=0 | | x^2+15x-490=0 | | -j+10s-j+12-8s= | | 8-(4x+m)=5(x+6)-2 | | (6x^4+6x^3-9)-(6x^2-4x+5)= | | 17+6y-10+m+7m= | | (-9p^3)(3p^5)= | | -3x+5y=25 | | 3(3y-2)=5(3y+2) | | 6+4m-17g+6m+3g= | | 11-1.5y=x | | 30x+9+9m+14x-3m= | | 4x-5=-2x+16 | | m+15c+(-3m)-4= | | 8-(4x+m)=5(x+6) | | 9m-14-6m+4r+12r= | | 7x+14-2x-5=3x+9+2x | | (x+6)(x+3)=340 |